2005
DOI: 10.1016/s0002-9440(10)62339-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Immune-Mediated Arrest of Tumorigenesis in a Transgenic Mouse Model of HER-2/neu-Positive Basal-Like Mammary Carcinoma

Abstract: We previously showed that a vaccine combining interleukin 12 and allogeneic p185 neu Immunological prevention of tumors is a feasible possibility especially in light of both the encouraging results obtained in preclinical models of neoplasia and of the recent advances in detection of healthy individuals at high risk of developing cancer. 1,2 Transgenic mice expressing the HER-2/neu oncogene under tissue-specific transcriptional control of the mouse mammary tumor virus promoter (MMTV-LTR) represent a suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…While their involvement in breast cancer has never been described, by exploiting data on the expression of miRNAs in human breast cancers [70,73], the over-expression of miR-135b, but not miR-135a, appeared to be associated with poor prognosis. In addition, miR-135b overexpression in basal-like and estrogen-negative human tumor shown by this meta analysis fits in well with the notion that mammary tumors of our HER-2 trasngenic mice are similar to basal-like and estrogen-negative human mammary carcinomas [76]. Down-modulation of miR-135b in cancer cells from HER-2 transgenic mice revealed its major role in anchorage-independent growth and lung metastasis formation.…”
Section: Discovery Of Novel Oncoantigens -Preneoplastic Lesions Diffsupporting
confidence: 87%
“…While their involvement in breast cancer has never been described, by exploiting data on the expression of miRNAs in human breast cancers [70,73], the over-expression of miR-135b, but not miR-135a, appeared to be associated with poor prognosis. In addition, miR-135b overexpression in basal-like and estrogen-negative human tumor shown by this meta analysis fits in well with the notion that mammary tumors of our HER-2 trasngenic mice are similar to basal-like and estrogen-negative human mammary carcinomas [76]. Down-modulation of miR-135b in cancer cells from HER-2 transgenic mice revealed its major role in anchorage-independent growth and lung metastasis formation.…”
Section: Discovery Of Novel Oncoantigens -Preneoplastic Lesions Diffsupporting
confidence: 87%
“…These findings were not unexpected because Mena protein, as well as the other members of the Ena/VASP family, localize to the focal adhesions, lamellipodial protrusions, and filopodia tips, where they control highly dynamic processes requiring a strict regulation of the actin cytoskeleton changes, such as fibroblast protrusion and migration (3), intracellular bacterial motility (19), and axon and dendritic guidance (20). A recent study on the gene expression signature in HER-2/neu-transgenic mice, a suitable model for mammary carcinogenesis, has shown Mena (ENAH) overexpression during HER-2-induced breast cancer progression (21), suggesting that signaling pathways related to different epidermal growth factor receptor family members may also modulate hMena. In line with these data, our results show a significant direct relationship between hMena and HER-2 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the mRNA expression profiles of Her2-positive tumors from microarray analysis [43,44]. However, validation of the long lists of biomarker candidates identified using either proteomic or genomic approaches is challenging.…”
Section: Identification Of Novel Biomarkersmentioning
confidence: 99%